I'm studying Sturm-Liouville theory and an exercise asks me:

Show the following when the linear second-order differential equation is expressed in self-adjoint form:

a) The Wronskian is equal to a constant divided by the initial coefficient $p$:

$$W(x) = \frac{C}{p(x)}$$

b) A second solution is given by

$$y_2(x) = Cy_1(x)\int^x \frac{dt}{p(t)[y_1(t)]^2}$$

As far as I know, a self-adjoitn form is something in the form:

$$\frac{d}{dx}\left[p(x)\frac{du(x)}{dx}\right] + q(x)u(x)$$

And the Wronskian of the two solutions $y_1, y_2$ of a general second order linear ODE, is $W(x) = y_1(x)y_2'(x)-y_1'(x)y_2(x)$. We also have that the wronskian can be expressed as

$$W(x) = W(a) \exp\left[-\int_a^xP(x_1)dx_1\right]$$

for some $a$ that I don't remember. Is there some connection between these formulas and what I need to prove?

Also, for b), I know that there is a method of finding a second solution based on the first solution, the wronskian, and the coefficients of the ODE, but how exactly should I do? I presume we have to use the wronskian above, but how?

  • $\begingroup$ You have the right idea on the first part, you basically need to rewrite your second order ODE as a system of first order ODE. The second part is an exercise about reduction of order technique, essentially you guess the second solution as $y_2(x) = v(x)y_1(x)$ for some $v_1(x)$. $\endgroup$ – Chee Han May 6 '17 at 20:42

For part (a), since you start with a self-adjoint second order linear differential operator, expanding this out gives: \begin{equation} p(x)y''(x) + p'(x)y'(x) + q(x)y(x) = 0. \tag{1} \end{equation} Let $y'(x)=z(x)$, then $$ z'(x) = y''(x) = -\frac{q(x)y(x) + p'(x)y'(x)}{p(x)} = -\frac{p'(x)z(x)}{p(x)} - \frac{q(x)y(x)}{p(x)},$$ assuming $p(x)$ is not the zero function. We can write this in a matrix form: $$ \begin{bmatrix} y' \\ z' \end{bmatrix} = \begin{bmatrix} 0 & 1 \\ -\frac{q}{p} & -\frac{p'}{p} \end{bmatrix} \begin{bmatrix} y \\ z \end{bmatrix} = A\begin{bmatrix} y \\ z \end{bmatrix}.$$ Now, using Abel's identity (which is the one you stated for the Wronskian), we obtain \begin{align*} W(x) & = W(a)\exp\left(-\int_a^x Tr(A(s))\, ds\right) \\ & = W(a)\exp\left(-\int_a^x \frac{p'(s)}{p(s)}\, ds\right) \\ & = W(a)\exp\left[-\ln(p(x)) + \ln(p(a))\right]\\ & = W(a)\exp\left[-\ln\left(\frac{p(x)}{p(a)}\right)\right] \\ & = W(a)\left(\frac{p(a)}{p(x)}\right) \\ & = \frac{C}{p(x)}, \end{align*} with constant $C=W(a)p(a)$.

For part (b), we guess an ansatz of the form $y_2(x) = v(x)y_1(x)$. Computing its first and second derivative: \begin{align*} y_2' & = v'y_1 + vy_1' \\ y_2'' & = v''y_1 + v'y_1' + v'y_1' + vy_1'' \\ & = v''y_1 + 2v'y_1' + vy_1'' \end{align*} Substituting this into (1) yields: \begin{align*} p[v''y_1 + 2v'y_1' + vy_1''] + p'[v'y_1 + vy_1'] + qvy_1 & = 0 \end{align*} Rearranging this yields: \begin{align*} v[py_1'' + p'y_1' + qy_1] + v''py_1 + 2v'py_1'+ v'p'y_1 & = 0 \end{align*} The term in the square bracket vanishes since $y_1$ is assumed to be a solution of (1). We are left with: \begin{align*} v''py_1 & = -v'[2py_1' + p'y_1] \\ v'' & = -\frac{v'[2py_1' + p'y_1]}{py_1} \\ v'' & = -v'\left(\frac{2y_1'}{y_1} + \frac{p'}{p}\right) \end{align*} Now, you only need to solve this separable second order ODE to obtain $v(x)$, which I will leave it to you.


The general formally selfadjoint form of a Sturm-Liouville operator is $$ Lf = \frac{1}{w(x)}\left[-\frac{d}{dx}\left(p(x)\frac{df}{dx}\right)+q(x)f\right] $$ where $w(x) > 0$ is a positive weight and $p(x) > 0$ also holds. The Lagrange identity for $L$ is \begin{align} (Lf)g-f(Lg) & = \frac{1}{w}\left[-(pf')'g + f(pg')'\right] \\ & =\frac{1}{w}\frac{d}{dx}\left(-(pf')g+f(pg')\right) \\ & =\frac{1}{w}\frac{d}{dx}W_p(f,g), \end{align} where $W_p(f,g)=p(fg'-f'g)$ is the weighted Wronskian. This gives the weighted inner-product identity $$ \int_{a}^{b}(Lf)gwdx - \int_{a}^{b}f(Lg)wdx = W_p(f,g)|_{a}^{b}, \\ (Lf,g)_w - (f,Lg)_w = W_p(f,g)|_{a}^{b}. $$ The Lagrange identity gives a reduction of order formula, which was discovered by Lagrange in the late 1700's for linear ODEs of second and higher orders. To see how such an identity arises, suppose $Lf=\lambda f$ is a known solution. Then a second solution $g$ of $Lg=\lambda g$ is obtained by using the Lagrange identity to obtain a reduced order equation: $$ 0 = \lambda f g - \lambda fg = (Lf)g-f(Lg) = \frac{1}{w}\frac{d}{dx}W_p(f,g). $$ That is, $g$ is obtained from a known solution $f$ by solving $W_p(f,g)=C$ using this known $f$: $$ p(fg'-f'g) = C \\ fg'-f'g = \frac{C}{p} \\ \frac{fg'-f'g}{f^2} = \frac{C}{pf^2} \\ \frac{d}{dx}\left(\frac{g}{f}\right) = \frac{C}{pf^2} \\ \frac{g}{f} = C\int \frac{1}{pf^2}dx + D \\ g = Cf \int \frac{1}{pf^2}dx + Df. $$ Nothing is lost by setting $D=0$ and later adding a linear combination of $g$ and $f$ for the general solution.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.